2011
DOI: 10.1007/s12272-011-0811-y
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of dl-praeruptorin a in rat liver microsomes using HPLC-electrospray ionization tandem mass spectrometry

Abstract: dl-Praeruptorin A (Pd-Ia) is the major active constituent of the traditional Chinese medicine Peucedanum praeruptorum Dunn. Recently it has been identified as a novel agent in the treatment and prevention of cardiovascular diseases. Accordingly, we investigated the metabolism of Pd-Ia in rat liver microsomes. The involvement of cytochrome P450 (CYP) and CYP isoforms were identified using a CYP-specific inhibitor (SKF-525A), CYP-selective inhibitors (α-naphthoflavone, metyrapone, fluvastatin, quinidine, disulfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…The polarity of Pd-la metabolites increased after hydroxylation and therefore the metabolites would be excreted easier than Pd-la from the body. The results confirmed that Pd-la metabolism is mediated by CYP3A1/2 and the metabolic changes in Pd-la may happen with other CYP3A inducers and/or inhibitors (drug-drug interactions) [ 75 ]. In a latest study, the kinetics of enzyme action and the main CYP450 isozyme(s) involved in the metabolism of (+)-praeruptorin A were considered in HLMs by a fast, sensitive, and reproducible UHPLC-QT-MS/MS (ultrahigh-performance liquid chromatography coupled with a hybrid quadruple-linear ion trap mass spectrometry) method.…”
Section: Pharmacokinetics and Tissue Distribution Studiessupporting
confidence: 58%
“…The polarity of Pd-la metabolites increased after hydroxylation and therefore the metabolites would be excreted easier than Pd-la from the body. The results confirmed that Pd-la metabolism is mediated by CYP3A1/2 and the metabolic changes in Pd-la may happen with other CYP3A inducers and/or inhibitors (drug-drug interactions) [ 75 ]. In a latest study, the kinetics of enzyme action and the main CYP450 isozyme(s) involved in the metabolism of (+)-praeruptorin A were considered in HLMs by a fast, sensitive, and reproducible UHPLC-QT-MS/MS (ultrahigh-performance liquid chromatography coupled with a hybrid quadruple-linear ion trap mass spectrometry) method.…”
Section: Pharmacokinetics and Tissue Distribution Studiessupporting
confidence: 58%
“…In this study, chemical inhibition was employed to identify specific CYP isoforms responsible for mono‐hydroxylation of SFG in RLMs. Chemical inhibition is a common and simple method for screening CYP isoforms of RLMs (Ruan and others ; Shi and others ), but chemical inhibition combined with other methods including recombinant CYPs, antibody neutralization, and correlation analysis is required in order to obtain accurate results (Yan and Caldwell ) because most chemical inhibitors inhibit more than one CYP isoforms. However, according to previously published reports, furafylline being a selective inhibitor for rat CYP1A2 (Eagling and others ; Kobayashi and others ) and diethyldithiocarbamate being a selective inhibitor for rat CYP2E1 (Liu and others ; Shi and others ), it can initially be considered that CYP1A2 and CYP2E1 played predominant roles in the mono‐hydroxylation of SFG.…”
Section: Discussionmentioning
confidence: 99%
“…Pyranocoumarins could be rapidly transported across the intestine via passive diffusion (Jing et al, ), but underwent cytochrome P450 (CYP450) and carboxylesterase (CES)‐mediated hydrolysis (Jing, Song, Yan, & Wang, ). After absorption into the systemic circulation, the oxidation and hydrolysis were two predominant metabolic pathways of these pyranocoumarins, which were mediated by CYP450 isoenzymes in liver microsomes (Ruan et al, ). Notably, considerable CYP3A4‐, CYP2A1‐ and CYP2C8‐mediated hydrolysis or oxidation of pyranocoumarins occurred during incubation with the liver microsome (Jing et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, considerable CYP3A4‐, CYP2A1‐ and CYP2C8‐mediated hydrolysis or oxidation of pyranocoumarins occurred during incubation with the liver microsome (Jing et al, ). Among these metabolites, khellactone was the common hydrolysis metabolite of praeruptorin A (Ruan et al, ), praeruptorin B and praeruptorin E (Song, Yan, Jing, Zhao, & Wang, ). Khellactone has long been used as a synthetic precursor to synthesize khellactone derivatives with antitumor, liver protection and anti‐AIDS activity (Jung et al, ; Liu et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation